Prevalence of Intestinal Parasites and Salmonella typhi among Food Handlers Working in Catering Establishments of Public Institutes Found in Dawuro Zone, South-Western Ethiopia - Abera Kumalo; Eyasu Gambura; Terfe Dodicho; Khawaja Shakeel Ahmed; Tamrat Balcha; Bahailu Beshir; Misrak Abraham (Journal of Parasitology Research)
Background. Food borne disease, which is the result of ingestion of foodstuffs contaminated with microorganisms, parasites, or chemicals, encompasses a wide spectrum of illness and public health problem worldwide. Ethiopia is placed on second, third, and fourth position due to the highest burden of ascariasis, hookworm, and trichuriasis, respectively, in sub-Saharan Africa. The present study is aimed at determining the prevalence of Salmonella typhi and intestinal parasites among food handlers working in catering establishments of public institutes found in Dawuro Zone, South-Western Ethiopia. Methods. A cross-sectional study is conducted among food handlers working in catering establishments of public institutions found in Dawuro Zone from March to July 2019. The data was collected by using pretested structured questionnaires. Stool and blood samples were taken from each participant for parasitic examinations concurrently using direct and modified formol ether concentration wet smear techniques and Widal test by slide test and tube serial dilution technique, respectively. The data entered into Epi info version 3.5.1 and then exported into SPSS window version 20.0 for analysis. Logistic regressions were performed to assess the association between binary outcomes and different explanatory variables. P value <0.05 was considered statistically significant. Result. The study included 402 (293 females and 109 males) food handlers. Of 402 stool specimens, 20.4% were found to be positive for different parasite species, comprising protozoa (35.9%) and helminths (64.1%). A. lumbricoides was the most prevalent parasite (8.0%), followed by E. histolytica/dispar (4.23%). Twenty-six (6.5%) of food handlers were positive for Widal test. Ages≥40 years (AOR: 0.436; 95% CI: 0.203, 0.937), attending no education (AOR: 2.142; 95% CI: 1.048, 4.378), not washing hands after using latrine (AOR: 4.355; 95% CI: 1.771, 10.708), not covering mouth with tissue paper (AOR: 0.530; 95% CI: 0.312, 0.899), no medical checkup (in the last four months) (AOR: 0.278; 95% CI: 0.116, 0.667), and untrimmed fingernails (AOR: 0.382; 95% CI: 0.229, 0.635) were significantly associated with intestinal parasitic or Salmonella typhi infections. Conclusion. The prevalence of intestinal parasitic infection (IPI) and Salmonella among food handlers in the present study is relatively high compared to other different studies conducted in developed and developing countries. Therefore, biannually screening of food handlers for intestinal parasites (IPs) and periodic deworming of infected cases along with provision of food safety measures focusing on personal hygiene and environmental sanitation are recommended to control the parasitic infection in food handlers.